In vitro study the Characterization of Azotobacter spp. isolates from Sudanese soils - M.M., Alsamowal; M.A, Hadad; .M.A, Mohammed; Elhassan4G.A. (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2016)
An attempt was made to look for indigenous , ecofriendly N2 fixing microorganismsinhabitant to Sudanese soils. Isolates were made from a clay soil in central Sudan, where most of the soils are classified as nitrogen deficient, and where most of the economical crops aregrown including sorghum , wheat, and sugarcane. The isolates were identified using standard methods as Azotobacter sp.Characterization of the isolates was made including morphological and physiological tests. The obtained results revealed similar results to what had been reported earlier in the literature.Tests were made for the isolates tolerance to different temperatures, different pHs, differentsalt concentrations, and to antibiotic resistance in a Mannitol N-free Agar Medium. The data collected indicated that Azotobacter isolates from Sudanese soils grow best in media with neutral pH (7) , tolerate temperatures in the mesophylic range (300C) , and can withstand salt concentrations from 0.2-0.4% NaCl. Further studies were stressed to look into their efficiency in fixing atmospheric nitrogen when exposed to the harsh environmental conditions prevailing in Sudan.